Penggajian Berbasis Mobile di Universitas Ma’soem - Encep Supriatna (Universitas Maso'em Bandung, 2020)
Design a Mobile Based Lecturer Payroll Information System at Ma’soem University to provide solutions to several lecturers who have limited time so they do not have time to fill in lecturer attendance after completing lectures so that it affects the work of the finance and curriculum sections,The approach method used is an object-oriented approach (object oriented) which consists of object-oriented analysis (OOA), and object-oriented design (OOD). The system development method used is prototype. While the author's modeling system uses Unified Modeling Language (UML).With the design of the lecturer payroll information system, it is expected to facilitate lecturers in completing attendance and seeing details of their income, the finance department does not have to work overtime to make lecturer salary reports, and the curriculum section is more facilitated in controlling lecturer performance.